Profil dan Efektivitas Terapi Pasien Glaukoma Rawat Jalan di Rumah Sakit di Yogyakarta - Annisa, Lily; Jasmine, Iqtafit Zachrofati; Violita, Nindhi Happy (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Glaukoma is one of the eye diseases that most often causes permanent blindness. The effectiveness of glaukoma therapy is generally assessed by the reduction of intraocular pressure and improvement of the patient's clinical condition. The research aims to examine the therapeutic profile and effectiveness of outpatient glaucoma patients in a hospital in Yogyakarta. Methods: This study is a descriptive observational study with a cross-sectional design. Data collection was carried out retrospectively through medical records of outpatients at hospitals in Yogyakarta in 2023-2024 with a purposive sampling method. Analysis of the relationship between treatment profiles and effectiveness was carried out using the Chi-square test. Results: In this study, patients with the use of antiglaukoma combination therapy regiments were more dominant (57.07%) with additional administration of supportive therapy of (71.73%). The combination of antiglaukoma groups of beta-blockers-prostaglandin analogs with the combination drug timolol-latanoprost was the most commonly administered drug (26.7%). Artificial tears (65.97%) are a supportive therapy often given in conjunction with antiglaukoma therapy. The analysis results showed there was no relationship between the therapy regiment (p = 0.41) or the type of therapy (p = 0.897) with the effectiveness of antiglaukoma drug therapy. Conclusion: Combination antiglaukoma therapy is given more often than monotherapy. The combination of timolol and latanoprost is the most commonly given regiment. The majority of patients received antiglaukoma along with supportive therapy. There was no relationship between the therapy regiment or the type of drug with the effectiveness of therapy.